EXPLORING THE PERCEPTIONS AND EXPERIENCES OF HEALTH ASSISTANT NURSING TECHNICIANS IN IMPLEMENTING EVIDENCE-BASED PRACTICE IN SAUDI HOSPITALS - Abdullah Gulaifs Al-Otaibi, ‏Naif Abdulaziz Al-Mutairi, ‏Nawaf Faleh Al-Mutairi, ‏Ahmed Mohammed Al-Mutairi, ‏Nader Abdulaziz Al-Mutairi, ‏Muhammad Hadian Al-Mutairi, ‏Meshal Hussein Al-Mutairi (Chelonian Research Foundation, 2022)
Background: Evidence-based practice (EBP) is crucial for delivering high-quality patient care and improving healthcare outcomes. Health assistant nursing technicians (HANTs) play a vital role in implementing EBP in clinical settings. This study aimed to explore the perceptions and experiences of HANTs in implementing EBP in Saudi hospitals. Methods: A qualitative descriptive study was conducted using semi-structured interviews with 20 purposively selected HANTs working in various healthcare settings in Saudi Arabia. The interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged from the data: (1) understanding of EBP, (2) barriers to implementing EBP, (3) facilitators of implementing EBP, and (4) strategies to promote EBP implementation. The participants demonstrated a basic understanding of EBP but identified several barriers, including lack of time, inadequate resources, and limited knowledge and skills. The facilitators included organizational support, teamwork, and personal motivation. The participants suggested various strategies to promote EBP implementation, such as providing education and training, involving HANTs in decision-making, and creating a supportive work environment. Conclusion: HANTs in Saudi Arabia face various challenges in implementing EBP, but they also recognize the importance of EBP in improving patient care. Healthcare organizations should provide the necessary support, resources, and training to enable HANTs to effectively implement EBP in their practice. Further research is needed to develop and evaluate interventions to promote EBP among HANTs in Saudi Arabia. Keywords: evidence-based practice, health assistant nursing technicians, perceptions, experiences, qualitative research, Saudi Arabia